Laboratory investigation of coal bottom ash modified warm mix asphalt - Zulfiqar Ali, Jattak; Norhidayah, Abdul Hassan; Mohd Khairul Idham, Mohd Satar; Putra Jaya, Ramadhansyah; Mohd Rosli, Hainin (Penerbit Universiti Teknologi Malaysia, 2021)
Bottom Ash (BA), a coal combustion by-product, found to be a potential material when used to produce asphalt mixture. However, some of its characteristics make it a questionable material for the surface course. Therefore, this study aims to evaluate the compatibility of BA in Warm Mix Asphalt (WMA) technology through the basic mechanical properties of the asphalt mixtures for binder course layer (AC 28). Two WMA chemical additives, Cecabase RT and Evotherm 3G, were used at the concentrations of 0.3, 0.4 and 0.5% from the binder's weight. The binder properties were assessed through penetration, softening point and viscosity tests. The Marshall mix design was used to determine the optimum binder content (OBC). The additive dosage and production temperature for WMA were determined through Marshall stability, flow, air voids and specific gravity. The results show that the additives did not significantly affect the binder properties, although, at 0.4% Evotherm 3G, a drop of 17.5% in penetration was observed. Cecabase RT produced WMA with promising results but did not enhance the workability of WMA containing bottom ash (BAWMA). By lowering the production temperature of 25 °C, WMA and BAWMA at 0.4 %, Evotherm 3G demonstrated comparable workability to the conventional Hot Mix Asphalt (HMA). The data achieved through this study would be a guiding approach towards the application of BA in WMA technology for sustainable pavements.